TINGKAT PENGETAHUAN AKSEPTOR KB IUD TENTANG EFEKSAMPING KB UD DI WILAYAH KERJA PUSKESMAS KEMBARAN I KABUPATEN BANYUMAS TAHUN 2008 - Tin Utami (Viva Medika, 2008)
The purpose of this research is to determine the level of knowledge about the IUDacceptors efeksamping IUD in Puskesmas Kembaran I Banyumas.This research method is a descriptive study with cross sectional approach.Samples were IUD acceptors with the number of 74 respondents drawn usingsimple random sampling technique.The result of this research is the IUD most respondents have sufficient knowledgeof as many as 33 respondents (44.6%), and the least is the respondents who haveless knowledge both as much as 16 respondents (21.6%).The conclusion in this study that the level of knowledge about the IUD acceptorsefeksamping IUD in Puskesmas Kembaran I Banyumas is enough. Keywords: knowledge of efeksamping IUD, IUD acceptors.